Exploring the Relationship Between Employees Wellbeing and Organizational Performance (Journal of Asian Development Studies, 2025)
The research area involves exploring the dynamic connection between employee well-being (high and low), employee engagement, and organisational performance, considering the moderating effect of leadership style. It also fills a significant research gap, considering that there is little literature evaluating the impact of various well-being levels on engagement and, consequently, upper organisational outcomes in a changing work environment. Employees from a series of organisations in the service sector in Pakistan served as the source of the data, collected through a quantitative cross-sectional design. Explorative tests of direct and moderated relationships were performed using a PLS-SEM approach. Measurement of constructs was conducted using validated Likert-scale items, and structural relationships were examined through bootstrapping in SmartPLS. The outcome indicates that both high well-being (0.350) and low well-being (0.408) are significant predictors of employee engagement, which has a strong influence on organisational performance (0.768). Leadership style moderation was poor (beta = 0.013), indicating that employee engagement may be more dependent on system well-being than on leadership behaviour.